Digitalisasi Pencatatan Tanah Adat dan Hak Ulayat Berbasis Blockchain untuk Keamanan Data Aset Desa - Nuna, Muten; Junus, Dikson; Arsjad, Muh. Fachri; Tabo, Sarfan; Ahmad, Sunandar (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2026)
This study aims to formulate a blockchain-based digitalization model for customary land registration and customary rights in Bone Bolango Regency. The urgency of this research is driven by the need to transform the traditional registration system, which still relies on manual archives and oral legitimacy, into a secure, transparent digital system that aligns with local wisdom. The theoretical framework used encompasses customary rights, digital governance, and blockchain governance. The research method utilizes an ethnographic approach through participatory observation, in-depth interviews with customary leaders, village officials, and the community, as well as analysis of historical documents and regulations related to customary land. The research findings indicate that customary land records in Bone Bolango are still vulnerable to loss, damage, and lack formal legal force, weakening the position of indigenous communities in disputes. On the other hand, the community, especially the younger generation and village officials, demonstrates openness to digitalization, despite limited digital literacy and infrastructure. The potential for blockchain implementation is identified through its advantages in ensuring data immutability, transparency, and its ability to integrate customary values through smart contracts. Blockchain can be a strategic solution to address the weaknesses of traditional record-keeping while strengthening social legitimacy and legal protection of customary rights. Bone Bolango Regency offers